IDENTIFYING FACTORS THAT AFFECT CHEESE CONSUMPTION AS ESSENTIAL ELEMENTS FOR ADEQUATE PLACEMENT ON THE REGIONAL MARKET - Kalenjuk, Bojana Miro; Ivanović, Velibor; Mitrović Milić, Anita; Radević, Danica; Novaković, Dragana; Đerčan, Bojan; Tešanović, Dragan; Milić , Zlatibor (Economics of Agriculture, 2024)
Cheese is a significant agri-food product for many people and the economy. Its manufacture has a long tradition, and its consumption varies according to the specifics of the cultures. Knowing consumers’ needs, attitudes, and approaches to consumption is essential in any industry, including the agri-food industry. That is why the subject of this paper is consumer behavior (CB), defining the factors that influence attitudes and intentions in cheese consumption observed at the level of two regions from Southeast Europe: the Republic of Serbia and Montenegro. The CB-Cheese scale was created for research purposes, which proved appropriate for this agri-food product research. The research showed significant differences in the behavior of the consumers of these two markets and that the consumption of cheese increases with the level of income. Special attention is paid to the quality of the product and its compatibility with the price. The obtained data provide clear guidelines for adequate placement in the regional market.